Definition of the "Purity Protocol" for Producing Gluten‐Free Oats. Issue 3 (30th January 2017) - Allred, Laura K.; Kupper, Cynthia; Iverson, Gary; Perry, Tracy B.; Smith, Seaton; Stephen, Robert
Abstract : Several oat processors in the United States and Canada operate under what is referred to as a Purity Protocol for the provision of gluten‐free oats. This term is derived from a Health Canada position statement that indicated that pure oats, which they defined as oats that are harvested, transported, stored, processed, and manufactured under good manufacturing practices (GMPs) to minimize the presence of gluten, can safely be consumed by some persons with celiac disease. While proprietary definitions of the appropriate GMPs have been used in industry for many years, no independent definition of the requirements to make a Purity Protocol claim has been published. This paper provides a consensus definition of the Purity Protocol requirements based on input from the four largest Purity Protocol oat processors in North America. This definition provides transparency to gluten‐free consumers and allows for auditing of a Purity Protocol claim.